Why No Clinic Is an Island: The Merits and Challenges of Integrating Clinical Insights Across the Law Curriculum - Jeff Giddings (Washington University Journal of Law & Policy, 2010)
In this Essay, Giddings presents a case study of the attempts to integrate clinical legal education throughout the curriculum in Australia. This study is both comprehensive and instructive. It illustrates familiar challenges to teaching a broad range of professionalism and lessons regarding justice while bringing real life problems and clients into the academy. It is also instructive regarding successful and unsustainable strategies. One of the main contributions of this Article is its objectivity. Giddings notes that much of the clinical pedagogical scholarship is about the authors’ own programs and lacks a certain sense of distance and skepticism. He thus provides a more detached and comparative perspective. In addition, Giddings studies the actual implementation of integration rather than the plans for such programs. Beside these methodological benefits, Giddings’ central contribution is his synthesis of the ingredients of successful integration of clinical pedagogy into the curriculum: sequencing, integration of clinical faculty into the courses, complementarities between clinic and podium courses. For Giddings, the benefits of integration inure to the students who learn reflection in action and to the clinic faculty who become more enmeshed in and central to the academy. Barriers include the difficulties in achieving economies of scale and of managing expectations. In other words, successful integration may demand more resources than the institution can sustain and may demand more of the clinical professors, who must be, in addition to teaching, of both the worlds of practice and research, while non-clinic colleagues need be engaged in teaching and scholarship, but not practice. This Article provides a road map toward integration into the classroom of professional values, the notion of actual human beings, and real problems of justice.
Keywords: Clinical legal education; Curriculum development; Law school